Altered cortical activation patterns in post-stroke patients during walking with two-channel functional electrical stimulation: a functional near-infrared spectroscopy observational study - Xu, Sheng; Zhu, Shizhe; Li, Minyao; Zhang, Tianjiao; Wang, Qinglei; Sui, Youxin; Shen, Ying; Chaojie, Kan; Zhuang, Ren; Guo, Chuan; Wang, Tong; Zhu, Lan (Frontiers in Neurology, 2025)
Restoration of independent walking ability is the primary objective of stroke rehabilitation; however, not all patients achieve this goal due to diverse impairments in the paretic lower limb and compensatory mechanisms that lead to an asymmetrical and mechanically inefficient gait. This investigation aimed to examine alterations in cortical activation in post-stroke patients while walking with a wearable two-channel functional electrical stimulation (FES) in comparison to walking without FES. This observational study was conducted to discern distinct activation patterns in 19 stroke patients during sessions with and without FES, while using functional near-infrared spectroscopy (fNIRS) to monitor changes in blood oxygen levels. Our findings revealed only a significant reduction in ΔOxy-Hb in the contralesional pre-motor cortex (z = −2.803, p = 0.005) during the FES-on walking sessions compared to the FES-off sessions. Furthermore, all regions in the FES-on session exhibited lower ΔOxy-Hb. Conversely, no significant differences were observed in ΔDeoxy-Hb. Moreover, a significant correlation was found between decrease in cPMC and the reduced cost time of walking under FES-on condition. The fNIRS analysis revealed diminished activation in the contralesional pre-motor cortex when walking with FES, implying that FES may facilitate a more automatic gait pattern while reducing a patient’s reliance on contralesional cortical resources. The findings of this study lay the groundwork for long-term neural rehabilitation.